Myelomatous Pleural Effusion: A Case Series - Thomas, Ajai; Thambi, Sugeeth M; Narayanan, Geetha; AV, Jayasudha; Prestine, Antony; Nair, Sreejith G (Asian Pacific Journal of Cancer Care, 2023)
Background: Extramedullary disease in multiple myeloma typically occurs at advanced stages and is associated with poor survival. Common extramedullary sites include the nasal cavity, lymph nodes, lungs, central nervous system, liver, spleen, skin, and orbit. Pleural effusions in multiple myeloma are unusual and rarely due to the myeloma itself, occurring in less than 1% of cases. Case Presentation: This case series described eight patients diagnosed with myelomatous pleural effusion at the Department of Medical Oncology in a tertiary cancer care center in India, between 2012 and 2018. Clinical presentation, diagnosis, treatment, and survival data were extracted from medical records. Results: The eight patients with myelomatous pleural effusion represented 0.45% of all multiple myeloma cases treated during the study period. Five of the eight patients were female, with a median age of 58 years. Three patients presented with myelomatous pleural effusion at initial diagnosis, while five developed it during disease progression. IgG was the most common immunoglobulin subtype. The International Staging System (ISS) stage was I in one patient and III in seven. After the diagnosis of multiple myeloma, all patients developed myelomatous pleural effusion at a median of 7 months, and all died within 2 weeks. Conclusion: Pleural effusions in multiple myeloma should be investigated to rule out myelomatous pleural effusion. Myelomatous pleural effusion is a rare manifestation of myeloma, characterized by an aggressive course and poor prognosis.